The Function of Language in Understanding Islamic Psychology in Islamic Educational Institutions: A Critical Literature Review - Husain, Andi Musthafa; Wantini, Wantini; Syaifussalam, Muhammad Lathief (Unisia, 2024)
This article aims to investigate and elaborate on key concepts in Islamic psychology, focusing on fithrah (nature), aql (intellect), nafs (self), and qalb (heart). As a primary concern, this research seeks to understand the interconnection between these four concepts and how their influence shapes human behavior and spiritual growth in the context of Islam. The research methodology involved an in-depth literature analysis of Islamic theological and philosophical sources. This approach allows researchers to explore the roots of thought and scholars' interpretations of fithrah, aql, nafs and qalb. Furthermore, this approach provides insight into how these concepts are applied in everyday life, especially in the context of education and personal development. The research findings indicate that fithrah, as inherent to human nature, plays a crucial role in guiding individuals toward spiritual and moral awareness. Aql, as a gift from Allah, grants humans the ability to think and understand, paving the way for the pursuit of knowledge and understanding of God. Nafs, as the internal dimension of humans, play a central role in self-development, understanding emotions, and maintaining a balance between worldly desires and spiritual aspirations. Qalb, or the heart, is considered the center of spirituality and moral values, requiring care to remain pure and draw closer to Allah. This article explores the implications of Islamic psychology concepts in the context of education and personal development. This research can serve as a foundation for the development of sustainable psychological approaches to holistically explore human potential, creating a balance between physical and spiritual dimensions. The final conclusion emphasizes the importance of integrating fithrah, aql, nafs, and qalb to shape a balanced and responsible human personality from an Islamic perspective.